Effect of atmospheric cold plasma on the quality of fish meat from different parts of larger yellow croaker during refrigeration - Yang, Chenyi; Cai, Jiaxi; Deng, Shanggui; Xu, Mengyuan; Dai, Huiqi; Shan, Sitong; Gao, Yuanpei; Yang, Ruizhi; Lan, Hao (Frontiers in Nutrition, 2026)
In this study, the effects of atmospheric cold plasma (ACP) as a non-thermal sterilization method on the quality of different muscle tissues parts in Large yellow croaker (Larimichthys crocea) during refrigerated storage were systematically investigated. The results of this study demonstrate that atmospheric cold plasma treatment (ACP, 40 kV, 90 s) significantly inhibited the accumulation of TVB-N and TBARS (p < 0.05) in fish samples while effectively mitigating the decline in water-holding capacity. Compared with the control group, the total sulfhydryl content in dorsal and ventral muscles increased significantly by 20 and 45%, respectively, and Ca2+-ATPase activity was also significantly enhanced by 14 and 20% (p < 0.05) after treatment. Furthermore, ACP treatment significantly maintained the color parameters (L, a, b*) and textural properties (hardness, elasticity, etc.) of fish meat (p < 0.05). ACP has an inhibitory effect on post-oxidation. GC–MS analysis detected 60 volatile compounds, with significantly reduced aldehyde levels in the treated group, demonstrating effective inhibition of undesirable flavor formation. These findings collectively indicate that ACP treatment effectively delays quality deterioration in fish during refrigerated storage through multiple synergistic mechanisms.